In vitro Models of Bone Remodelling and Associated Disorders - Owen, Robert; Reilly, Gwendolen C. (Frontiers in Bioengineering and Biotechnology, 2018)
Disruption of bone remodelling by diseases such as osteoporosis results in an imbalance between bone formation by osteoblasts and resorption by osteoclasts. Research into these metabolic bone disorders is primarily performed in vivo; however, in the last decade there has been increased interest in generating in vitro models that can reduce or replace our reliance on animal testing. With recent advances in biomaterials and tissue engineering the feasibility of laboratory-based alternatives is ever increasing; however, to date there are no established in vitro models of bone remodelling. In vivo¸ remodelling is performed by organised packets of osteoblasts and osteoclasts called bone multicellular units (BMUs). The key determinant of whether osteoclasts form and remodelling occurs is the ratio between RANKL, a cytokine which stimulates osteoclastogenesis, and OPG, its inhibitor. This review initially details the different circumstances, conditions and factors which have been found to modulate the RANKL:OPG ratio, and fundamental factors to be considered if a robust in vitro model is to be developed. Following this, an examination of what we have achieved thus far in replicating remodelling in vitro using three-dimensional co-cultures is performed, before overviewing how such systems are already being utilised in the study of associated diseases, such as metastatic cancer and dental disorders. Finally, a discussion of the most important considerations to be incorporated going forward is presented. This details the need for the use of cells capable of endogenously producing the required cytokines, application of mechanical stimulation, and the presence of appropriate hormones in order to produce a robust model of bone remodelling.